2015
DOI: 10.1002/cne.23785
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal organization of the brain in the adult amphioxus (Branchiostoma lanceolatum): A study with acetylated tubulin immunohistochemistry

Abstract: Amphioxus (Cephalochordata) belongs to the most basal extant chordates, and knowledge of their brain organization appears to be key to deciphering the early stages of evolution of vertebrate brains. Most comprehensive studies of the organization of the central nervous system of adult amphioxus have investigated the spinal cord. Some brain populations have been characterized via neurochemistry and electron microscopy, and the overall cytoarchitecture of the brain was studied by Ekhart et al. (2003; J. Comp. Neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 129 publications
(210 reference statements)
0
22
0
Order By: Relevance
“…Although there are significant differences in the nervous systems created from this early territory among the deuterostomes, the ANE initially arises from a relatively simple, flat neuroepithelium during the early stages of development and many of the cell types that this territory produces are remarkably conserved (Burke et al, 2014;Castro et al, 2015;Cavodeassi, 2013;Garner et al, 2015;Pani et al, 2012;Range, 2014). Based on the spatial and temporal expression of ANE regulatory genes in several species, it appears that the ANE gene regulatory network (GRN) hierarchy is also remarkably conserved among many deuterostome embryos, suggesting that these could be homologous territories (Range, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are significant differences in the nervous systems created from this early territory among the deuterostomes, the ANE initially arises from a relatively simple, flat neuroepithelium during the early stages of development and many of the cell types that this territory produces are remarkably conserved (Burke et al, 2014;Castro et al, 2015;Cavodeassi, 2013;Garner et al, 2015;Pani et al, 2012;Range, 2014). Based on the spatial and temporal expression of ANE regulatory genes in several species, it appears that the ANE gene regulatory network (GRN) hierarchy is also remarkably conserved among many deuterostome embryos, suggesting that these could be homologous territories (Range, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the LB processes might repress the startle reaction and contribute to the hovering of larvae during swimming. Later in development compact LB disaggregates (possibly due to forward expansion of JCs), since only scattered lamellate cells were detected in adults (Castro et al, 2015;Meves, 1973). As described earlier, amphioxus larvae display a typical circadian rhythm guided behavior (diurnal migration), while adults live mostly borrowed in the sand during both day and night.…”
Section: Lamellar Bodymentioning
confidence: 56%
“…In larvae, JCs are probably located posterior to the LB, while in adults the JCs form a cap above the scarce lamellate cells. About 400-450 JCs are present in the adult amphioxus (Castro et al, 2015). Studies of the ultrastructure of JCs confirmed their rhabdomeric character.…”
Section: Rhabdomeric Photoreceptorsmentioning
confidence: 88%
“…The existence of photoreceptors in the central nervous system appears to be an ancestral feature in chordates, because the brain and spinal cord of amphioxus contains at least four different populations of photoreceptors (Koyanagi, Kubokawa, Tsukamoto, Shichida, & Terakita, ; Castro, Becerra, Manso, Sherwood, & Anadón, ; Castro, Becerra, Manso, & Anadón, ; Vopalensky et al, ). Non‐mammalian vertebrates possess a wide range of intrinsically photoreceptive sites expressing members of the non‐visual opsin family (see Hankins, Davies, & Foster, ).…”
Section: Discussionmentioning
confidence: 99%